2020
DOI: 10.3988/jcn.2020.16.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Incidental Neuroimaging Abnormalities in New Primary Headache Patients

Abstract: Background and Purpose Deciding whether or not to perform neuroimaging in primary headache is a dilemma for headache physicians. The aim of this study was to identify clinical predictors of incidental neuroimaging abnormalities in new patients with primary headache disorders. Methods This cross-sectional study was based on a prospective multicenter headache registry, and it classified 1,627 consecutive first-visit headache patients according to the third edition (beta version) of the International Classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The proportion of incidental findings discovered was similar to that of the significant findings, and also to that reported for patients with a new primary headache [16]. Kim et al reported incidental abnormalities in 25% of new primary headache patents scanned with MRI, of which white matter hyperintensities and sinonasal abnormalities not related to headache were the most common.…”
Section: Discussionsupporting
confidence: 78%
“…The proportion of incidental findings discovered was similar to that of the significant findings, and also to that reported for patients with a new primary headache [16]. Kim et al reported incidental abnormalities in 25% of new primary headache patents scanned with MRI, of which white matter hyperintensities and sinonasal abnormalities not related to headache were the most common.…”
Section: Discussionsupporting
confidence: 78%
“…The current study reveals that, for Korean patients specifically, the proportion is much higher at 48%. MRI was the most common diagnostic test among respondents, followed by CT, possibly due to MRI being more sensitive than CT in identifying intracranial pathology, and more generally preferred for the evaluation of headaches [32][33][34]. Neuroimaging is not usually warranted for patients who meet the diagnostic criteria for migraine and have normal findings on a neurologic examination.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Moreover, the prevalence of incidental brain lesions in an asymptomatic population is the same as those presenting with headache, increasing with age in both groups. 24,25 In this study, symptoms suggestive of a raised ICP headache had a strong negative predictive value of CNS cancer, suggesting that, paradoxical to traditional beliefs, with such features the likelihood of CNS cancer is low. This is consistent with cohorts of patients presenting with 'headache of raised ICP' that have shown that neither is this higher in patients with brain tumour nor is it an indicator for raised ICP.…”
Section: Headachementioning
confidence: 56%
“…25,34 This is no different in patients with headache outside the context of thunderclap headache. 24,25 Yet, nevertheless, the tendency to intervene occurs. This is clear from a meta-analysis showing imaging abnormalities in headache patients similar to previous studies, prompting the authors to recommend imaging for headache.…”
Section: Role Of Direct Access Imagingmentioning
confidence: 99%